ANALISIS KONTRIBUSI JASA PELAYANAN KAPAL PEMANDUAN DAN PENUNDAAN TERHADAP PENERIMAAN NEGARA BUKAN PAJAK PADA KANTOR UNIT PENYELENGGARA PELABUHAN KELAS II TANJUNG REDEB: ANALISIS KONTRIBUSI JASA PELAYANAN KAPAL PEMANDUAN DAN PENUNDAAN TERHADAP PENERIMAAN NEGARA BUKAN PAJAK PADA KANTOR UNIT PENYELENGGARA PELABUHAN KELAS II TANJUNG REDEB - Darmono Darmono (Prodi Ekonomi Pembangunan, Universitas Muhammadiyah Berau, 2022)
Analysis of the Contribution of Guiding and Towing Ship Services to Non-Tax State Revenues at the Tanjung Redeb Class II Port Operator Unit Office. The purpose of this study was to determine the development of the contribution of Guiding and Towing Ship Services to non-tax state revenues at PT. Pelabuhan Indonesia IV (Persero) Tanjung Redeb. Based on the results of the contribution and regression analysis, the hypothesis is rejected, because based on the results of the analysis, although the effect is positive and strong, the contribution of Guiding and Towing Ship Services has decreased to non-tax state revenues at PT. Pelabuhan Indonesia IV (Persero) Tanjung Redeb